The multidimensional summation formula of Euler—Maclaurin - Bikelis, A. (Lithuanian Mathematical Journal, 1968)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. Формула суммирования Эйлера — Маклорена для функций многих переменных A. Bikelis. Eilerio—Makloreno sumavimo formulė daugelio kintamųjų funkcijoms